Recensiones - J. R. J.,; J. M. G.,; Ellacuría, Ignacio; I. E.,; S. M. A., (ECA: Estudios Centroamericanos, 1970)
No hay resúmenes disponibles.ECA Estudios Centroamericanos, Vol. 25, No. 258, 1970: 155-160.